Was Buddha a prophet? - Khattab, Mohammad Ali (Advances in Social Sciences Research Journal, 2020)
This research is a view of the life of Buddha in his childhood, in the palace of his father, and his religious education taught by Hindu monks of the Brahmins. He has reached a prestigious position in knowledge. The research also dealt with the stage of his young adulthood, his marriage, son and family. The report also reviewed the stage of searching for the truth in the forest, accompanying a group of his friends, and then the report spoke of the despair that entered Buddha's heart by not arriving a result, and how he left the forest and the way of austerity. The research spoke about the Enlightenment obtained under the tree of knowledge, as a logical result of the journey of asceticism, worship and mutilation. The research also touched on the Buddha's call and principles; followed by his students and disciples, and the conditions he developed for the individual to become Buddhist. Buddha's campaign was not an ordinary religious call; it became preponderant that Buddha may have been a prophet, after a comprehensive account of the evidences that accompanied it, but a host of internal and external obstacles diverted the religion from its origin, and moved it from its nature, to claim the divinity of the Buddha afterwards.